Quality of life and symptoms of pain in patients with endometriomas compared to those with other endometriosis lesions: a cross-sectional study - Fleur Serge Kanti; Valérie Allard; Sarah Maheux-Lacroix (BMC Women's Health, 2024)
Abstract Background Endometriomas are genetically distinct from other endometriosis lesions and could be associated with a predisposition to excessive inflammation. However, differences in clinical presentation between types of endometriosis lesions have not been fully elucidated. This study aimed to investigate the quality of life and pain scores of patients with endometriomas compared to those with other types of endometriosis lesions. Methods A cross-sectional observational study was conducted between January 2020 and August 2023. Patients diagnosed with endometriosis completed the Endometriosis Health Profile 30 pain subscale questionnaire for their quality of life score and rated their endometriosis-associated pain symptoms using an 11-point numerical rating scale. The data were analyzed for comparison through multivariate linear regression models. Results A total of 248 patients were included and divided into endometrioma (81, 33%) and nonendometrioma (167, 67%) groups. The mean age of the patients was 37.1 ± 7.5 years. Most participants were Canadian or North American (84%). One-third of the patients reported experiencing up to four concurrent pain symptoms. The most reported pain included deep dyspareunia (90%), chronic pelvic pain (84%) and lower back pain (81%). The mean quality of life score was 45.9 ± 25.9. We observed no difference in quality of life scores between patients with and without endometriomas. Patients with endometriomas had lower mean scores for deep dyspareunia (0.8; 95% CI [0 to 1.5]; p = 0.049) and higher mean scores for superficial dyspareunia (1.4; 95% CI [0.2 to 2.6]; p = 0.028). Comorbid infertility (p = 0.049) was a factor that modified superficial dyspareunia intensity in patients with endometriomas. Conclusion In patients with endometriosis, evidence was insufficient to conclude that the presence of endometriomas was not associated with a greater or lesser quality of life, but differences in specific symptoms of dyspareunia were identified.